Analysis of Traffic Performance and Handling Scenarios in the Malang Station Area, Kota Baru - Prakosa, Dandun; Jamhari, Syafek; Veronica, Veronica; Irfan Efendi, Ade (Publisher Cv. Inara, 2026)
The Malang Kota Baru Station area is currently experiencing traffic performance problems characterized by high delays and low speeds, especially on the Trunojoyo 1 Road and Trunojoyo 2 Road sections. This condition is influenced by high side obstacles in the form of on-street parking and loading and unloading activities. This study aims to analyze the performance of the existing road network and formulate effective traffic management and engineering scenarios in improving regional traffic performance. The analysis was carried out by modeling using PTV Vissim software through the calibration and validation stages using the Geoffrey E. Havers (GEH) statistical test. The results of the analysis of existing conditions showed an average delay of 168 seconds, network speed of 13.6 km/h, total mileage of 24,120 kend-km, and total travel time of 1,774 vehicles/hour, which indicates that the performance of the road network is in the poor category. Improvement efforts are carried out through several traffic management and engineering scenarios, including moving on-street parking to off-street, repairing pedestrian facilities, adding signs and repairing road markings, as well as regulating the separation of access in and out of goods and passengers. The results of the proposed scenario simulation showed an improvement in road network performance, namely an increase in network speed to 22.04 km/h, a decrease in average delay to 90.91 seconds, a decrease in total travel time to 1,160.59 vehicles/hour, and an increase in total mileage to 25,574 kend-km. Thus, the proposed traffic management and engineering scenario has proven to be effective in improving traffic performance in the Malang Kota Baru Station Area.